Rebellion as a learning experience in the light of narrations of adults participating in protests. Selected issues - Przemyslaw Szczygiel (European Journal for Research on the Education and Learning of Adults, 2022)
The aim of this article is to show the learning potential of participation in protests in the narratives of several adults. Participation in rebellions is seen as a specific learning experience here. What is the relationship between experience and learning on the example of participation in rebellions? The author analyses this relationship, inter alia, on the example of critical practices described by Usher. This article is a part of a broader research project on learning mechanisms of adults participating in various forms of rebellion. The study is concerned with answering the questions: what and how do protesters learn? what are the social and cultural mechanisms of their learning? In this research project a biographical perspective was used. Within it, the biography is understood in a processual way. The biographical method focuses on the subjective level of experience in the socio-cultural and institutional context. The empirical material was analysed by searching for similarities and differences in rebels’ narratives. The results of the study are above all the identification of learning outcomes and identity-building processes.